Pengaruh Pendampingan Suami terhadap Percepatan Kala I Fase Aktif pada IBu Bersalin di Aulia Hospital Pekanbaru - Mardiah, Hanifatul (AHM Center, 2026)
Acceleration of the active phase of the first stage in mothers giving birth accompanied by their husbands Mothers who are accompanied by their husbands generally experience the active phase of the first stage of labor for less than 6 hours, indicating a more optimal acceleration of labor compared to mothers who are not accompanied. The presence of a husband provides emotional and physical support, reduces anxiety, and increases the effectiveness of uterine contractions. This study aims to determine the effect of husband's assistance on the acceleration of the active phase of labor. The analysis shows a significant difference between mothers who are accompanied and not accompanied by their husbands. The type of research used is Quaesi experimental. The number of samples is 20 respondents selected by purposive sampling. The results of this study indicate that there is a very significant relationship between husband's assistance and the acceleration of the active phase of labor in mothers giving birth at Aulia Hospital Pekanbaru in 2025. Of the 11 mothers who received husband's assistance, 10 people (90.9%) experienced accelerated labor with a duration of <6 hours, while in the group who did not receive husband's assistance, all respondents (100%) actually experienced a longer labor (>6 hours). The Fisher's Exact Test statistical test provides a statistically significant p value < 0.001, so it can be concluded that husband's support has been proven to have an effect on accelerating the labor process.